1985
DOI: 10.1161/01.res.57.4.545
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a possible role of the brain kallikrein-kinin system in the modulation of the cerebral circulation.

Abstract: SUMMARY. Experiments by others have shown that exogenous bradykinin dilates cerebral arterioles and that the brain contains kininogen and kallikrein, the latter being the enzyme which converts kininogen to bradykinin. The objective of these experiments was to determine if bradykinin produced from endogenous brain kininogen can affect the cerebral microcirculation. Rabbit pial arteriolar diameter was measured with a microscope using the dosed cranial window technique. Topical application of bradykinin (10~8-10~… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(8 citation statements)
references
References 40 publications
(34 reference statements)
0
8
0
Order By: Relevance
“…However, the EDRF for calcium ionophore in brain microvessels may be identical to that for bradykinin, another agent of potential pathophysiologic importance. 25 The EDRF for bradykinin is also cyclooxygenase dependent. 25 The diameter changes we observed averaged 7-11% for calcium ionophore and ACh.…”
Section: Discussionmentioning
confidence: 99%
“…However, the EDRF for calcium ionophore in brain microvessels may be identical to that for bradykinin, another agent of potential pathophysiologic importance. 25 The EDRF for bradykinin is also cyclooxygenase dependent. 25 The diameter changes we observed averaged 7-11% for calcium ionophore and ACh.…”
Section: Discussionmentioning
confidence: 99%
“…- 25 In cats and mice, bradykinin-induced cerebral vasodilatation appears to be mediated by generation of oxygen radicals. 1 -2 Our preliminary study showed that bradykinin-induced cerebral vasodilatation in rats was almost completely inhibited by catalase.…”
mentioning
confidence: 99%
“…At least two mechanisms could be involved: (i) a depletion of local tissue kininogen stores, or (ii) occupation of neural receptor sites by continuously formed endogenous kinins. A depletion of brain kininogen has been implicated in the desensitization of rabbit pial arterioles to the second dose of kallikrein, since the arterioles still responded normally to exogenous bradykinin (Kamitani, Little & Ellis, 1985). In the present experiments, tachyphylaxis to kallikrein was associated with a long-lasting (up to 60 min) reduction of reflexogenic effects of exogenous kinins, but not that of capsaicin which also involves activation of cardiac afferents incorporated in spinal thoracic sympathetic nerves (StaszewskaWoolley et al 1986).…”
Section: Effects Of Epicardial Treatment By Aprotininmentioning
confidence: 45%